A GROUP OF GLASS VESSELS IN SAMSUN MUSEUM - Temür, A.; Özbilgin, Ö. (Материалы по археологии и истории античного и средневекового Причерноморья, 2024)
Glass, which has evolved continuously since its discovery, was initially used by the wealthy classes, but over time, with advancements in construction technologies and increased production speed, it became widely adopted across all levels of society. Glass vessels used in daily life became an important part of societal life. The collections of the Samsun Museum contain a large number of glass vessels. The items under study in this publication were acquired through purchase, donation, or confiscation. The fact that most artifacts are wellpreserved suggests that they likely originate from burial contexts. Evaluating these items is crucial for understanding the political, commercial, and cultural organization of the period in which they were used, as well as their geographical distribution. Additionally, detailed analysis can provide insights into the place of production of the vessels. The glass artifacts from the Samsun Museum collections represent common forms, with similar examples identified in various regions. The study results indicate that Eastern Mediterranean culture had a broad distribution, extending throughout Anatolia. Glass vessels were produced in similar forms across the extensive territory governed by the Roman Empire, reflecting the dominant cultural norms of the period. Therefore, precise information on the origin of the vessels is difficult to establish. This challenge is also compounded by the lack of evidence for glassmaking furnaces in the region. Thus, it may be hypothesized that these vessels could be of imported origin. Nevertheless, it should be considered that Amisos and Neoklaudiopolis — important cities in the region— would have been unlikely to ignore the production or trade of glass as a valuable commercial resource.